Multi-Objective Optimization Method for the Shape of Large-Space Buildings Dominated by Solar Energy Gain in the Early Design Stage - Zhang, Longwei; Wang, Chao; Chen, Yu; Zhang, Lingling (Frontiers in Energy Research, 2021)
A large-space building features a sizable interface for receiving solar radiation, optimizing its shape in the early design stage can effectively increase its solar energy harvest while considering both energy efficiency and space utilization. This study develops a large-space building shape optimization method based on the “modeling-calculation-optimization” process to transform the “black box” mode in traditional design into a “white box” mode. First, a two-level node control system containing core space variables and envelope variables is employed to construct a parametric model of the shape of a large-space building. Second, three key indicators, i.e., annual solar radiation, surface coefficient, and space efficiency, are used to representatively quantify the performance in terms of sunlight capture, energy efficiency, and space utilization. Finally, a multi-objective genetic algorithm is applied to iteratively optimize the building shape, and the Pareto frontier formed by the optimization results provides the designer with sufficient alternatives and assesses their performance. Further comparative analysis of the optimization results can reveal the typical shape characteristics of the optimized solutions and potentially determine the key variables affecting building performance. Through the case study of six typical shapes of large space buildings, it is found that compared with reference building 1 and 3, the solar radiation of the optimized buildings shape solutions increases by 13.58-39.74%; Compared with reference building 2 and 4, they also achieve the optimal balance of the three key indicators. The results show that the optimization method can effectively improve the comprehensive performance of the building.